Penerapan Akuntansi Zakat (PSAK No. 109) pada Wakaf Infaq Sadaqah (Studi pada Wakaf Infaq dan Sedekah (WIZ) Kabupaten Bone - sari utami; Septia Ismail (Jurnal Akuntansi dan Keuangan Syariah (Jurnal Akunsyah), 2023)
Currently, an Islamic-based economy has become a necessity for the people. The economic empowerment of the ummah is increasingly being carried out by several Islamic financial institutions. They are trying so that the Islamic economy is not only an alternative for Muslims, but indeed it must be the only option for them. This is to prevent the ummah from all kinds of ribāwi financial practices carried out by conventional banks. In addition, the utilization of zakat, donations/alms originating from Muslims must be managed as early as possible by professional zakat management institutions so that they can be distributed effectively and on target as part of an effort to empower the people's economy.       This research belongs to the scope of financial accounting research, because it discusses accounting treatment, measurement, recognition, reporting systems, and company policies. Based on the characteristics of the problem, this research is classified as descriptive research. The research approach used is a qualitative approach, namely a study that intends to understand the phenomenon of what is experienced by research subjects such as behavior, perceptions, motivations, actions and others in a holistic manner and by means of descriptions in the form of words and language, in a special natural context and by making use of various natural methods.       Zakat funds were obtained from muzakki who came directly to the amil zakat agency (WIZ) in Bone district and received a receipt as proof of receipt of zakat where the first sheet of the note was given to the muzakki and the second sheet was kept by the amil zakat agency. And the distribution of zakat funds is directly given directly to 8 asnaf who are entitled to receive and record the distribution of zakat funds. In the recording of the amil zakat agency (WIZ) in Bone district where it uses a double entry system when zakat funds are distributed it will reduce zakat funds. Zakat accounting treatment according to PSAK 109 has been implemented but not optimal. One of the reasons is that zakat amil bodies in general are from departments that are less basic regarding zakat accounting. The form or model for calculating zakat accounting at WIZ Bone district presents a report on financial position, a cash flow statement, and a report on changes in funds.             Keywords: Accounting, Reports, WIZ, Zakat.